2016
DOI: 10.15252/embr.201642771
|View full text |Cite
|
Sign up to set email alerts
|

Natural mutations in IFITM3 modulate post‐translational regulation and toggle antiviral specificity

Abstract: The interferon-induced transmembrane (IFITM) proteins protect host cells from diverse virus infections. IFITM proteins also incorporate into HIV-1 virions and inhibit virus fusion and cell-to-cell spread, with IFITM3 showing the greatest potency. Here, we report that amino-terminal mutants of IFITM3 preventing ubiquitination and endocytosis are more abundantly incorporated into virions and exhibit enhanced inhibition of HIV-1 fusion. An analysis of primate genomes revealed that IFITM3 is the most ancient antiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
130
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(142 citation statements)
references
References 57 publications
5
130
1
Order By: Relevance
“…The minor allele of rs12252 has been associated with HIV progression in a Chinese cohort 35 . However, the predicted truncation mutant mediated by rs12252 8 , which has not been observed in published studies, was able to restrict HIV replication 36 , so this association may indicate a role for other effects of this locus.…”
Section: Discussionmentioning
confidence: 60%
“…The minor allele of rs12252 has been associated with HIV progression in a Chinese cohort 35 . However, the predicted truncation mutant mediated by rs12252 8 , which has not been observed in published studies, was able to restrict HIV replication 36 , so this association may indicate a role for other effects of this locus.…”
Section: Discussionmentioning
confidence: 60%
“…The differential susceptibility of viruses to IFITM3‐mediated restriction has revealed that IFITM3 inhibits infections by viruses that enter cells through endocytosis . Indeed, IFITM3 primarily localizes to endosomes and lysosomes , and IFITM3 mutants that alternatively localize to the plasma membrane possess a diminished ability to inhibit influenza virus infection . Taken together, these findings indicate that IFITM3 acts within the endolysosomal pathway.…”
Section: Introductionmentioning
confidence: 94%
“…This 1F1TM3 polymorphism is predicted to cause alternative splicing of the transcript, resulting in truncation and altered localization of IFITM3, though the existence of a shortened form of IFITM3 remains to be conclusively demonstrated (39). Recent work in vitro suggests that although this alteration of IFITM3 decreases antiviral activity against influenza virus, its activity against retroviruses is increased (29), thus revealing a potential selective advantage for the SNP that may explain its high prevalence in certain human populations (177). Additionally, given that IFITM3 antiviral activity is highly regulated by at least four posttranslational modifications, polymorphisms in factors that install or remove these modifications and impact influenza virus susceptibility may be uncovered in the future (2224, 117, 172).…”
Section: Influenza Virusmentioning
confidence: 99%